Immobilization of DNA - Nor Azah, Yusof, Assoc. Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Institute of Nano Electronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th June 2011 at Tun Za'ba Seminar Room, Unit Kesihatan & Keselamatan Pekerjaan, Seriab Campus, Perlis, Malaysia.